The Research of Molded Bra Cup Inner Surface and Its Capacity (Journal of Fiber Bioengineering and Informatics, 2014)
Different bra cup inner surface leads to different capacity and style in dress. As a result, it is importantto consider inner surface and its capacity in bra cup designing. In this paper, molded cup with wires isviewed as the research subject: its 3D model is rebuilt in Geomagic Studio, and its capacity is definedand measured in Unigraphics. Then a wearing experiment is conducted where one model wears moldedcup bras of same size but different inner surfaces to study bra push-up and upgrade function and byanalyzing the difference between cup capacity and breast volume. The research result is that the biggerdifference between cup capacity and breast, the greater its influence on breasts. Moreover, with similartotal bra cup capacity, the push-up and upgrade functions of bra cups in different degrees are presented.Furthermore, molded bra cup is split to blocks and analyzed in order to examine the impact on differentfunctions. There is a certain guiding principle to inner surface shape design of molded bra cup.